A Systematic Mapping of Approaches and Techniques in Object Navigation - Turossi, Marcos Tulio Costa; Ribeiro, Carlos Eduardo; Almeida, Diogo Henrique de; Silva, Mateus de Oliveira; Todt, Eduardo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
Object navigation (ObjectNav) is a widely used method for visual perception tasks in 3D environments. ObjectNav is based on the use of a variety of technologies and approaches, with a particular focus on semantic navigation. This systematic literature mapping (SLM) study aims to provide a comprehensive overview of the state of the art in this area, identify trends and gaps in current research, and recommend direction for future work. We systematically searched for five key scientific databases: ACM Digital Library, IEEE Digital Library (IEC), Google Scholar, CAPES Journals, and Web of Science. Our inclusion and exclusion criteria led to the identification of 28 relevant articles. The results of our systematic mapping are instrumental in understanding the current landscape of object navigation and in identifying promising avenues for future research.